2010
DOI: 10.2341/10-157-l
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Quality of Self-adhesive and Conventional Adhesive Resin Cement to Y-TZP Ceramic Before and After Aging Conditions

Abstract: Clinical RelevanceChairside tribochemical silica coating and silanization on the YTZP surface appears to be essential to adhere this substrate to resin cements. Cleaning with isopropanol promotes weak and unstable resin adhesion. Conditioned ceramics were divided into four groups to receive the resin cements (Panavia F 2.0, Variolink II, RelyX U100 and Maxcem). After 24 hours, half of the specimens (n=12) from each group were submitted to shear bond strength testing (0.5 mm/minute). The remaining specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 39 publications
1
47
0
8
Order By: Relevance
“…It is reaction site, and these sites are limited, which means that the chemical effect has an upper limit that cannot be overcome [15,28]. Also in this work, the group without surface treatment dramatically decreased the bond values when submitted to thermal cycling probably because the sorption of water must have caused the degradation of adhesive interface during aging [6].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…It is reaction site, and these sites are limited, which means that the chemical effect has an upper limit that cannot be overcome [15,28]. Also in this work, the group without surface treatment dramatically decreased the bond values when submitted to thermal cycling probably because the sorption of water must have caused the degradation of adhesive interface during aging [6].…”
Section: Discussionmentioning
confidence: 78%
“…The metal / zirconia primer improves bond strength only in initial condition and that after thermal cycling, all specimens became loose [22]. In a survey, the group without surface treatment, several samples became loose after thermal cycling, but tribochemical treatment enhances the bond strength [6]. Specimens without surface treatment became loose in storage in water after 90 days; however, silica coating after immersion in water increased its bond strength [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tribochemical silica coating (e.g., Rocatec or CoJet system, 3M ESPE) is a commonly used and commercial technique, which air-abrades Zirconia surface with alumina particles that have been coated with nano-silica, resulting the impregnation of nano-silica into the Zirconia surface. Studies showed tribochemical silicacoating followed by silanation significantly enhanced bond strengths between zirconia and resin materials (Xible et al, 2006;Ozcan et al, 2011;Passos et al, 2010), but it was not clear whether it was caused by silica-coating or the surface roughening effect of airabrasion. After silica-coating, different silence might have different effects on resin-Zirconia bond strengths.…”
Section: Non-silica-based Zirconia Ceramicsmentioning
confidence: 99%